Automatic Enrichment of Croatian Morphological Lexicon Using Large Corpora and Web Search - Merkler, Danijela (Array, 2012)
Inflectional (or morphological) lexica are considered to be language resources of high importance and frequent usage in many language processing tasks -- from basic problems such as lemmatization and morphosyntactic tagging of written text to applications in machine learning, information extraction, information retrieval and machine translation -- for highly inflectional languages such as Croatian. Being that Croatian Morphological Lexicon (HML) is frequently used both as a stand-alone application and as a module in many other systems for processing Croatian, unknown wordforms -- those undetected when matching unseen text with the current version of the HML database -- are constantly being logged and the lexicon is being updated to newer versions by inserting these new wordforms in batches. Accordingly, in this paper, we propose a generic approach to (semi-)automatic generation of new candidate lemmas for HML, their verification, assignment of inflectional patterns and finally creation and insertion of new lexicon entries to HML in a single processing pipeline.